STRATEGI GURU TAHFIZ QUR’AN DALAM MENINGKATKANHAFALAN AL-QUR’AN SANTRI DI PESANTREN ADLANIYAHMODERN KECAMATAN LEMBAH MELINTANG KABUPATEN PASAMAN - Waston, Waston (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
The problem of this research is that there are still schools that have tahfidz programs but have not been able to print students in memorizing the Qur'an properly. Even though it is a pesantren, the modern Adlaniyah of the valley of the transverse district is able to print students in memorizing the Qur'an according to the makharujul letters and tajwid. This study aims to find out how the efforts of Tahfidz teachers in improving the memorization of the Qur'an of students. This research is a field research with a qualitative descriptive approach. This research began to be carried out in June-October 2021. The subjects in this study were Tahfidz teachers. while the informants were the principal, other teachers besides Tahfidz teachers, the head of the Tahfidz coordinator, and students. Data collection techniques were carried out by means of observation, interviews, and documentation. In testing the validity of the data used triangulation of sources and methods. Then the data was analyzed using an interactive analysis model with the following steps: data collection, data reduction, data presentation, and drawing conclusions. fun when teaching and learning in class, 2) Providing time for students who want to deposit their memorization, 3) Murojaah letter juz 30 which is the target of student memorization, 4) Motivating students, 5) Giving gifts to students, 6) Giving additional hours of lessons for Tahfizul Qur'an, 7) Create a WA group for parents, 8) Coordinate with the principal. While the supporting and inhibiting factors in improving the memorization of the Qur'an of students are 1) Internal factors. Supporting factors are the conduciveness of students in the classroom. Meanwhile, the obstacle in improving the memorization of the Qur'an by the students is the lack of self-confidence from within the students. 2) External Factors. The supporting factor is the collaboration with the parents of students. While the obstacle is the lack of parental support for their children, they only surrender to school.